2014
DOI: 10.1016/j.yjmcc.2014.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Nox2 mediates high fat high sucrose diet-induced nitric oxide dysfunction and inflammation in aortic smooth muscle cells

Abstract: Diet-induced obesity and metabolic syndrome are important contributors to cardiovascular diseases. The decreased nitric oxide (NO) bioactivity in endothelium and the impaired response of smooth muscle cell (SMC) to NO significantly contribute to vascular pathologies, including atherosclerosis and arterial restenosis after angioplasty. Sarco/endoplasmic reticulum Ca2+ ATPase (SERCA) is an important mediator of NO function in both endothelial cells and SMCs, and its irreversible oxidation impair its stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…Aortic wall stiffening was associated with increased inflammation, as measured by cytokines TNFα, MCP-1, MIP1α, decreased nitric oxide (NO) bioavailability, and increased extracellular matrix cross-linking in the aortic wall 16 . We further demonstrated that, in the setting of dietary obesity, TNFα-induced activation of the oxidant-generating enzyme NADPH oxidase, Nox2, is a major determinant of inflammation associated with functional impairment of aortic smooth muscle cells 17 . VSM cell functional alterations have recently emerged has important determinants of vascular stiffening, contributing ∼ 50% to aortic stiffness 18-20 .…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Aortic wall stiffening was associated with increased inflammation, as measured by cytokines TNFα, MCP-1, MIP1α, decreased nitric oxide (NO) bioavailability, and increased extracellular matrix cross-linking in the aortic wall 16 . We further demonstrated that, in the setting of dietary obesity, TNFα-induced activation of the oxidant-generating enzyme NADPH oxidase, Nox2, is a major determinant of inflammation associated with functional impairment of aortic smooth muscle cells 17 . VSM cell functional alterations have recently emerged has important determinants of vascular stiffening, contributing ∼ 50% to aortic stiffness 18-20 .…”
Section: Introductionmentioning
confidence: 75%
“…Our previous work showed a link between HFHS-feeding, arterial stiffness and the production of oxidants in the aortas of obese mice, leading to inflammation and functional impairment in VSM cells, associated with increases in TNFα 16, 17 . Therefore, we assessed whether the amelioration of arterial stiffness by SirT1 activators and genetic overexpression of SirT1 were mediated by anti-inflammatory and anti-oxidant effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations